2000
DOI: 10.1128/jvi.74.24.11495-11503.2000
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Immediate-Early 1 (m123/pp89) Peptide-Specific CD8 T Cells in a Pulmonary CD62LloMemory-Effector Cell Pool during Latent Murine Cytomegalovirus Infection of the Lungs

Abstract: . 74:7496-7507, 2000). It was proposed that these cells represent antiviral "standby" memory cells whose functional role might be to help prevent reactivation of latent virus. The pool of pulmonary CD8 T cells was composed of two subsets defined by the T-cell activation marker L-selectin (CD62L): a CD62Lhi subset of quiescent memory cells, and a CD62L lo subset of recently resensitized memory-effector cells. In this study, we have continued this line of investigation by quantitating CD8 T cells specific for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
209
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(227 citation statements)
references
References 57 publications
18
209
0
Order By: Relevance
“…CMV-infected mice show a marked increase in the percentage of CMVspecific CD8 + T cells during the latent phase of infection (100 to 400 days after infection [44,45]) and we here showed that analogous to the human situation, these late CMV-specific CD8 + T cells at peripheral sites had a CD27 -phenotype. CD27 expression is down modulated after repetitive interactions with its ligand, CD70.…”
Section: Discussionsupporting
confidence: 62%
“…CMV-infected mice show a marked increase in the percentage of CMVspecific CD8 + T cells during the latent phase of infection (100 to 400 days after infection [44,45]) and we here showed that analogous to the human situation, these late CMV-specific CD8 + T cells at peripheral sites had a CD27 -phenotype. CD27 expression is down modulated after repetitive interactions with its ligand, CD70.…”
Section: Discussionsupporting
confidence: 62%
“…These emerged as having “effector‐memory” profiles as judged by the expression pattern of molecules such as CCR7, CD62L, CD28, CD27, and CD127 (all low) 3, 16, 17. This molecular pattern suggests homing to non‐lymphoid tissues and indeed the second feature is accumulation not only in blood and spleen where it was first noted but in many such tissues such as lung and liver, as opposed to lymph nodes 1, 3, 13. The third feature observed was maintained effector functions such as cytokine release—in contrast to exhausted CD8 + T cells 8.…”
Section: The Origins Of Memory Inflationmentioning
confidence: 95%
“…Some of these have been discussed already as they are embedded in the definition—an effector‐memory phenotype as defined by lack of expression of lymph node homing markers such as CCR7 and CD62L 3, 13. It is certainly also the case that cells found in lymph nodes with these specificities retain expression of or re‐express such molecules, although these are a minority (in proportion) 50…”
Section: What Is Memory Inflation Now?mentioning
confidence: 99%
“…10,11 IFN-g-based ELISPOT analyses were carried out as detailed by others. 32 Values given represent the mean number of spots of triplicate wells and the standard deviation. (b) ELISPOT analysis of dendritic cells (DC), incubated with DB.…”
mentioning
confidence: 99%